2013
DOI: 10.1007/s13280-013-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

From Site Data to Safety Assessment: Analysis of Present and Future Hydrological Conditions at a Coastal Site in Sweden

Abstract: This paper presents an analysis of present and future hydrological conditions at the Forsmark site in Sweden, which has been proposed as the site for a geological repository for spent nuclear fuel. Forsmark is a coastal site that changes in response to shoreline displacement. In the considered time frame (until year 10 000 ad), the hydrological system will be affected by landscape succession associated with shoreline displacement and changes in vegetation, regolith stratigraphy, and climate. Based on extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the modeling of the clay domain, transport through the underlying till was neglected, in order to focus on the retention processes in the clay. Hydrodynamic processes and parameters were based on MIKE SHE model results (Graham and Butts 2005; Butts and Graham 2008; Berglund et al 2013).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In the modeling of the clay domain, transport through the underlying till was neglected, in order to focus on the retention processes in the clay. Hydrodynamic processes and parameters were based on MIKE SHE model results (Graham and Butts 2005; Butts and Graham 2008; Berglund et al 2013).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Our model of the waterborne transport of radionuclides between compartments is based on detailed hydrological modeling studies with MIKE-SHE (Graham and Butts 2005; Butts and Graham 2008; Berglund et al 2013b). These studies have shown that the vertical hydrological fluxes in the deep regolith layer of sea basins and bays are minute.…”
Section: Resultsmentioning
confidence: 99%
“…The studied soils give rise to a large range of K d values and it is not reasonable to apply the full range to model radionuclide transport in all agricultural soils (Avila et al 2013). Instead, the K d values should be matched with the modeled geographical distribution of different regolith types and land uses (Lindborg et al 2013) in relation to the probable discharge areas for deep groundwater (Berglund et al 2013). Peat and clay gyttja commonly occur in discharge areas and the properties of arable land on these regolith types are consequently of large importance for the safety assessment.…”
Section: Discussionmentioning
confidence: 99%